Secreted Flavin Cofactors for Anaerobic Respiration of Fumarate and Urocanate by Shewanella oneidensis: Cost and Role - Kees, Eric D.; Pendleton, Augustus R.; Paquete, Catarina M.; Arriola, Matthew B.; Kane, Aunica L.; Kotloski, Nicholas J.; Intile, Peter J.; Gralnick, Jeffrey A. (Applied and environmental microbiology, 2019)
Shewanella species are prevalent in marine and aquatic environments, throughout stratified water columns, in mineral-rich sediments, and in association with multicellular marine and aquatic organisms. The diversity of niches shewanellae can occupy are due largely to their respiratory versatility. Shewanella oneidensis is a model organism for dissimilatory metal reduction and can respire a diverse array of organic and inorganic compounds, including dissolved and solid metal oxides. The fumarate reductase FccA is a highly abundant multifunctional periplasmic protein that acts to bridge the periplasm and temporarily store electrons in a variety of respiratory nodes, including metal, nitrate, and dimethyl sulfoxide respiration. However, maturation of this central protein, particularly flavin cofactor acquisition, is poorly understood. Here, we quantify the fitness cost of flavin secretion and describe how free flavins are acquired by FccA and a homologous periplasmic flavoprotein, UrdA. Shewanella oneidensis strain MR-1, a facultative anaerobe and model organism for dissimilatory metal reduction, uses a periplasmic flavocytochrome, FccA, both as a terminal fumarate reductase and as a periplasmic electron transfer hub for extracellular respiration of a variety of substrates. It is currently unclear how maturation of FccA and other periplasmic flavoproteins is achieved, specifically in the context of flavin cofactor loading, and the fitness cost of flavin secretion has not been quantified. We demonstrate that deletion of the inner membrane flavin adenine dinucleotide (FAD) exporter Bfe results in a 23% slower growth rate than that of the wild type during fumarate respiration and an 80 to 90% loss in fumarate reductase activity. Exogenous flavin supplementation does not restore FccA activity in a Δ bfe mutant unless the gene encoding the periplasmic FAD hydrolase UshA is also deleted. We demonstrate that the small Bfe-independent pool of FccA is sufficient for anaerobic growth with fumarate. Strains lacking Bfe were unable to grow using urocanate as the sole electron acceptor, which relies on the periplasmic flavoprotein UrdA. We show that periplasmic flavoprotein maturation occurs in careful balance with periplasmic FAD hydrolysis, and that the current model for periplasmic flavin cofactor loading must account for a Bfe-independent mechanism for flavin transport. Finally, we determine that the metabolic burden of flavin secretion is not significant during growth with flavin-independent anaerobic electron acceptors. Our work helps frame the physiological motivations that drove evolution of flavin secretion by Shewanella . IMPORTANCE Shewanella species are prevalent in marine and aquatic environments, throughout stratified water columns, in mineral-rich sediments, and in association with multicellular marine and aquatic organisms. The diversity of niches shewanellae can occupy are due largely to their respiratory versatility. Shewanella oneidensis is a model organism for dissimilatory metal reduction and can respire a diverse array of organic and inorganic compounds, including dissolved and solid metal oxides. The fumarate reductase FccA is a highly abundant multifunctional periplasmic protein that acts to bridge the periplasm and temporarily store electrons in a variety of respiratory nodes, including metal, nitrate, and dimethyl sulfoxide respiration. However, maturation of this central protein, particularly flavin cofactor acquisition, is poorly understood. Here, we quantify the fitness cost of flavin secretion and describe how free flavins are acquired by FccA and a homologous periplasmic flavoprotein, UrdA.